Implementasi Metode Windowing Rectangular, Hamming, Hann, dan Kaiser pada Filter Finite Impulse Response (FIR) menggunakan Raspberry Pi - Binariesya Maulydia; M. Nanak Zakaria; Waluyo Waluyo (Jurnal Jaringan Telekomunikasi, 2020)
The use of digital filters is needed by electronic systems, such as in signal and audio processing. The use of digital filters is to filter frequencies and modify the frequency spectrum of a signal so that the desired goal is obtained. The purpose of the filter is a series that passes a certain desired frequency band and dampens other frequency bands. The method used in designing the FIR filter is using the windowing method. There are several techniques included in the windowing method, namely rectangular, hamming, hanning, and kaiser. For the windowing work system it really depends on the type of window used, therefore there is a comparison between the four. This research will be developed by designing a digital FIR filter that is implemented on the raspberry pi device which is expected to be well integrated using the simulink matlab. So a study was made that raised the problem of how to process digital signals to apply the FIR filter using the windowing method that was simulated using the matlab program and implemented on raspberry pi. From the test results, it can be seen that the Raspberry pi can be integrated well using the Simulink matlab. The bigger the ripple, the stopband attenuation, and the bandwidth width on the result of the signal output frequency response affect the resulting order, that is, the smaller it is.